Two new species of Cypricercinae McKenzie, 1971 (Crustacea: Ostracoda) from Thailand - Savatenalinton, Sukonthip (European Journal of Taxonomy, 2021)
Two new species of the subfamily Cypricercinae McKenzie, 1971 are described from the Western part of Thailand: Pseudostrandesia ratchaburiensis sp. nov. and Strandesia prachuapensis sp. nov. Pseudostrandesia ratchaburiensis sp. nov. is mainly characterized by a flange on the antero-ventral part of the left valve (LV), a markedly large β seta on the mandibular (Md) palp, serrated bristles on the third endite of the maxillula (Mx1), a slender caudal ramus (CR) with a long claw Ga (length ca half that of the ramus) and a relatively low number (13) of spiny whorls in the Zenker’s organ. The discovery of both males and females of Pseudostrandesia ratchaburiensis sp. nov. in the present study constitutes the first report of a sexual population in this genus, thereby allowing for a comparison of the male reproductive organs (hemipenis and Zenker’s organ) from a new species with those of other genera of Cypricercinae. Strandesia prachuapensis sp. nov. is most closely related to Strandesia odiosa (Moniez, 1892) and Strandesia flavescens Klie, 1932 as they bear similar anterior flanges on the right valve (RV). The key diagnostic features of the new Strandesia species are a large carapace (ca 1.5 mm), an angulated antero-ventral part of the LV, a weak and small anterior inner list on the LV, an anterior flange on the RV, a markedly small aesthetasc Y on the second antenna, a large β seta on the Md-palp, smooth bristles on the third endite of the Mx1 and a slender CR with a short claw Ga (length ca ⅓ of the ramus). In addition, Pseudostrandesia complexa (Victor & Fernando, 1981) comb. nov. is here proposed.